Factor Xa Cleavage of Tissue Factor Pathway Inhibitor Is Associated with Loss of Anticoagulant Activity - Salemink, Irene; Franssen, Jo; Willems, George M.; Hemker, Coenraad H.; Li, Anguo; Wun, Tze-Chein; Lindhout, Theo (Thrombosis and Haemostasis, 1998)
Tissue factor : factor VIIa induced activation of blood coagulation is inhibited by the complex between factor Xa and tissue factor pathway inhibitor (factor Xa : TFPI). We recently reported that phospholipid-bound factor Xa reduces the high binding affinity of factor Xa : TFPI for negatively charged phospholipids by a partial degradation of TFPI (17). The present study was undertaken to elucidate the factor Xa cleavage sites in TFPI and to delineate the consequences of this proteolysis with respect to the inhibitory activity of factor Xa : TFPI. We found that phospholipid-bound factor Xa cleaves in TFPI the peptide bonds between Lys86-Thr87 and Arg199-Ala200. Interestingly, Arg199 is the P1 residue of the third Kunitz-type protease inhibitor domain. The fast cleavage of the Arg199-Ala200 bond results in a 50-70% reduction of the anticoagulant activity of factor Xa : TFPI, as determined with a dilute tissue factor assay, but is not associated with a diminished inhibitory activity of factor Xa : TFPI towards TF : factor VIIa catalyzed activation of factor X. On the other hand, the slower cleavage of the Lys86-Thr87 peptide bond was associated with both a diminished anticoagulant and anti-TF : factor VIIa activity. Dissociation of factor Xa from the cleaved TFPI was not observed. These data provide evidence for a dual role of factor Xa since it is the essential cofactor in the TFPI-controlled regulation of TF-dependent coagulation as well as a catalyst of the inactivation of TFPI.